Plant–parasite coevolution: A weak signature of local adaptation between Peruvian Globodera pallida populations and wild potatoes. Issue 9 (15th April 2020) - Gautier, Camille; Fournet, Sylvain; Piriou, Christophe; Renault, Lionel; Yvin, Jean‐Claude; Nguema‐Ona, Eric; Grenier, Eric; Montarry, Josselin
Abstract: Plant–parasite coevolution has generated much interest and studies to understand and manage diseases in agriculture. Such a reciprocal evolutionary process could lead to a pattern of local adaptation between plants and parasites. Based on the phylogeography of each partner, the present study tested the hypothesis of local adaptation between the potato cyst nematode Globodera pallida and wild potatoes in Peru. The measured fitness trait was the hatching of cysts which is induced by host root exudates. Using a cross‐hatching assay between 13 populations of G. pallida and root exudates from 12 wild potatoes, our results did not show a strong pattern of local adaptation of the parasite but the sympatric combinations induced better hatching of cysts than allopatric combinations, and there was a negative relationship between the hatching percentage and the geographical distance between nematode populations and wild potatoes. Moreover, a strong effect of the geographic origin of root exudates was found, with root exudates from south of Peru inducing better hatching than root exudates from north of Peru. These results could be useful to develop new biocontrol products or potato cultivars to limit damages caused by G. pallida . Abstract : The present study tested the hypothesis of local adaptation between the potato cyst nematode Globodera pallida and wild potatoes in Peru, using a cross‐hatching assay between 13 populations of G. pallida and root exudates from 12 wild potatoes.